Personalized and predictive medicine in Turkey: A symposium report of the Istanbul Working Group on Personalized Medicine, Istanbul, Turkey, September 10-12, 2009 - (:unkn) unknown (Bentham Science Publishers, 2009)
Pharmacogenetics has its roots in the 1950s with pioneering studies of monogenic variations in drug metabolism and pharmacokinetics. With the availability of high-throughput genomics technologies and the completion of the Human Genome Project in 2003, we are now in the postgenomics era. This transition is increasingly marked with study of polygenic and multifactorial traits such as common complex human diseases as well as pharmacodynamic differences among populations. Changes that emerge from postgenomics medicine are not, however, limited to seismic shifts in scale and scope of pharmacogenetics research. Importantly, many low- and middle-income countries (LMICs) of the South, Asia-Pacific, Eastern Mediterranean and the Middle-East are becoming notable contributors with rapid globalization of science and increasing access to genomics technologies. This brings about, in parallel, an acute demand for regional capacity building in LMICs so that the future evaluation and implementation of postgenomics technologies in personalized medicine take place in an integrated, sustainable and equitable manner. With this overarching vision, we herein report the founding of the Istanbul Working Group in Personalized Medicine (IWG-PM, represented by the authors of this report) that was inaugurated as a component of the 2nd Symposium on Personalized and Predictive Medicine held in Istanbul, sponsored by the Yeditepe University, and the Turkish Scientific and Technological Research Council (TUB?TAK) (10-12 September, 2009). While highlighting the applications of personalized medicine in oncology, psychiatry, nutrition, infectious diseases, occupational health, genetic testing and systems biology, the symposium also raised challenging questions in the context of LMICs. How can we best evaluate the promises, intended and unintended impacts of personalized medicine and enabling technologies in the context of Turkey, and the LMICs more generally? IWG-PM is a small but significant and necessary step to initiate regional capacity building in Turkey. We trust that the IWG-PM initiative may also provide a constructive example to further develop capacity in other LMICs in the Eastern Mediterranean region. © 2009 Bentham Science Publishers Ltd.
Keywords: LMICs; Lower and middle income countries; Personalized medicine; Pharmacogenomics-guided pharmacovigilance; Regional capacity building